Renesančne knjižne vezave na slovenskih protestantskih tiskih v knjižnici Narodnega muzeja Slovenije v Ljubljani - Svoljšak, Sonja (Knjižnica, 2004)
The article presents a codicolodical census of five renaissance bookbindings on Slovene reformation prints from the library of the National Museum of Slovenia. Four of these prints: two Dalmatin's Bibles, Dalmatin's Lepe karszhanske molitve and Trubar's Hishna postilla have leather stiff board decorative renaissance bindings while Bohorič's Arcticae horulae succisivae has a stiff board vellum binding. A short overview of the European renaissance bookbindnig characteristics and decorative motives development is presented in the first part, followed bz the codicological census. The second part of the research consists of decorative tools and motives clasiffication and an individual motive analysis. An overview of the decorative motives on four decorative reformation bindings in the context of the European reformation book decoration styles with special emphasis on the Wittemberg reformation book decoration style is given in the final analysis.
Keywords: knjižne vezave; knjigoveštvo; renesansa; Protestantism; protestantizem; muzejske zbirke